Prospective randomized comparative study between EBRT alone and EBRT with ILRT boost in locally advanced unresectable esophageal cancer - Tertiary rural Indian cancer center experience - Sarahiya, Pinky; Rawat, Shyamji; Patel, Lalit M; Sharma , Hitesh; Singotia, Laxmi; Jain, Rajesh Kumar; Raychaudhuri , Arkojyoti (Asian Journal of Medical Sciences, 2024)
Background: Local recurrence within the gross tumor volume following a conventional radiation dose of 50 Gy is a major hurdle in achieving a better prognosis for esophageal carcinoma. Consequently, there remains a lack of consensus globally regarding the optimal dose for definitive concurrent chemoradiotherapy. Certain studies propose that radiation dose escalation could enhance clinical outcomes. Aims and Objectives: The current study aimed to compare the safety and effectiveness of external beam radiotherapy (EBRT) alone versus EBRT with intraluminal radiotherapy (ILRT) boost. Materials and Methods: A total of 60 patients with locally advanced unresectable squamous cell carcinoma of the esophagus were prospectively enrolled in this study. A comparison was conducted between 50 Gy EBRT alone and 50 Gy EBRT with 8 Gy ILRT boost, alongside weekly concurrent chemotherapy, to assess the response and toxicities. Results: On initial assessment, a complete response (CR) was achieved in 76.66% of patients in the ILRT boost arm and 70% in the EBRT alone arm (P=0.559). At the 6th-month follow-up, 60% of patients in the ILRT boost arm and 50% in the EBRT alone arm still had a CR. No statistically significant differences were observed between the two arms in terms of leukopenia (P=0.576), nephrotoxicity (P=1.0), radiation dermatitis (P=0.615), vomiting (P=0.921), and diarrhea (P=1.0). Five patients in the ILRT boost arm and three in the EBRT alone arm experienced stricture, while no cases of fistula formation were reported. Conclusion: Dose escalation with ILRT can result in an enhanced CR accompanied by manageable toxicity, ultimately leading to improved locoregional control.